Optimizing Rambak Cracker Production: Evaluating the Influence of Different Drying Methods on Protein, Fat, and Organoleptic Properties - Amertaningtyas, Dedes; Sintiya; Kalle, Amalia Dzulhaj Mutia; Abdilah, Riki; Evanuarini, Herly; Widyastuti, Eny Sri; Hermanto, Feri Eko; Saleha, Rischa Amalia (Faculty of Animal Science, Universitas Brawijaya, 2024)
Rambak crackers are made from cattle hides through the process of cleaning, threshing the hair and boiling. The research objective was to determine the physicochemical qualities of fresh cowhide, boiled cowhide, dried rambak crackers (krecek) and fried rambak crackers from 3 drying methods, namely, sun (M), oven (O), and sun oven (MO) drying methods. The material used was local cowhides from the slaughterhouse in Malang city. This experimental and counting method used a randomized block design with 3 treatments and 6 replications. The descriptive results showed that the average protein content in fresh cowhide, cecek and krecek was 36.18-84.97%, and the average ash content was 0.14-0.32%. The experimental results revealed k values of 170.40-217.54%, moisture contents of 16.55-18.22%, Aw values of 0.68-0.73, L values of 37.56-38.83, a* values of 0.58-1.26, and b* values of 6-6.98. The average fat content of the fried rambak crackers after sun, oven and sun oven drying was 5.83-29.06%, the average moisture content was 3.77-5.05%, the average aroma was 3.9-4.6, the average shape was 3.1-3.5, and the average preference was 2.5-3.3. In conclusion, 3 drying methods based on physicochemical and organoleptic properties can be applied and are preferred by panelists because drying using the oven method also has potential for cowhide crackers.